PENGARUH STATUS SOSIAL DAN PHYSICAL APPEARANCE TERHADAP LAMANYA WAKTU TUNGGU MENCARI KERJA PERTAMA KALI BAGI ANGKATAN KERJA SEKTOR FORMAL DI KOTA DENPASAR - Ni Putu, Yuni Astika Sari; A.A Bagus Putu, Widanta; I Ketut, Sudibia (PIRAMIDA; Vol 15 No 1 (2019): PIRAMIDA`- Jurnal Kependudukan dan Pengembangan Sumber Daya Manusia, 2019)
Economic development will certainly be better with a labor force that has a good per capita income as well, but with the phenomenon of the labor force who are more concerned about the positions and types of jobs to be taken they tend to prefer - selects in finding work. By looking at the imbalance between the number of labor force and current job opportunities, the workforce should not choose jobs, which will lead to unemployment. Most of the workforce in Bali, especially in Denpasar City chooses a job in accordance with the education that is being rescued. This phenomenon because one of the requirements to enter the work world is to have a high education, with the labor force certainly want to get a job in accordance with the education that was rescued. In addition there are also choosing a job in accordance with the wages earned, because of their higher life expenses.The purpose of this study is to analyze the influence of independent variables namely: Age, Expenditure, Education, Sex, and Physical Appearance to the dependent variable namely: the length of waiting time to find work. In this study using a hundred respondents as a sample who has been interviewed in depth in order to obtain primary data processed using multiple linear analysis method. The results of the processed showed that two variables did not significantly influence the gender variable and Physical Appearance but the rest had significant effect. Of all the independent variables, the most dominant educational variables affect the length of waiting time for work. With the value of determination korfisien of 0.326 which means able to explain 32.6 percent of variation in the length of waiting time looking for work, while the remaining 67.4 percent can be explained by other variables that are not included in the analysis model of this study. With a significance value of 0.000 smaller than 0.05 then the regression model can be used to predict the length of waiting time to find work and it can be said that all independent variables together affect the length of waiting time looking for work.